The effect of primary nursing care on the patients' ‎perception of nursing care behavior after coronary ‎angioplasty - Shahnaz Tabiei; Seyyed Ali Moezi; Gholamreza Sharifzadeh; Bahare Zarei; Fatemeh Kobra Shafiei (Tehran University of Medical Sciences, 2020)
Background & Aim: Cardiovascular diseases, especially coronary artery disease, are one of the most common causes of death worldwide. Recently, coronary intervention through the skin has been used for treatment, which has significantly reduced mortality rates. Nursing care behavior is of special importance in reducing the complications of angioplasty. The purpose of this study was to determine the effect of primary nursing care on the patients' perception of nursing care behavior after coronary angioplasty. Methods & Materials: In this randomized controlled clinical trial, 60 patients admitted from February 2018 to April 2018, to the CCU of Razi hospital in Birjand were selected by the convenience sampling method and assigned into two groups of 30, using a simple random allocation method. For the patients in the control group, routine care was delivered case by case, and for the patients in the primary nursing care group, care was provided based on the nursing process. At the time of discharge, the Caring Behaviors Inventory (CBI) was completed for the patients via interviews. Data were analyzed using the independent t-test and the significance levels of 0.05. Results: The results showed that the mean scores of perception of care behavior and dimensions "respect" and "assurance of humanistic presence" in the intervention group were significantly higher than those of in the control group (P<0.05). However, no significant differences were observed between the two groups in the dimensions "positive attitude and relationship", "knowledge and professional skill" and "attention to other experiences" (P>0.05). Conclusion: Provision of primary nursing care leads to improving the patient's perception of nursing care behavior, increasing sense of respect, and assurance of humanistic presence of the nurse. Therefore, it is recommended to use this caring method in the cardiac intensive care unit.